Cation synergy in Sr and Al substituted LaMnO3 during solar thermochemical CO2 splitting. (14th December 2022) - Nair, Mahesh Muraleedharan; Abanades, Stéphane
Abstract : The influence of bond polarity on the thermochemical redox properties of a series of cation substituted perovskite oxygen carriers is reported. Abstract : Perovskites (ABO3 ) constitute an important category of oxygen carriers for applications in thermochemical redox processes. This study aims to derive the relationship of cation dependent parameters including the tolerance factor ( τ ), critical radius ( R c ), free volume ( V F ), electronegativity ( χ ), and metal–oxygen bond energy ( λ ) with O2 /CO evolution efficiencies during redox steps of La x Sr1− x Mn y Al1− y O3 ( x = 0.4, 0.5, and 0.6 and y = 0.4, 0.5, 0.6, and 0.75) perovskite series. Such parameters can reflect the lattice structural variations and bond polarity in these materials. The observed trends of O2 /CO evolution are nearly reversed, with regard to the variations in cation constitution. Inconclusive correlations were observed for τ, R c, and V F during reduction and re-oxidation, indicating that the role of these parameters in representing the observed redox behaviour is limited. In contrast, the cation electronegativities and metal–oxygen bond energies were found to induce a significant impact in depicting the redox chemistry of these materials. Rather than the individual effects, the entire cationic constituents are found to synergistically influence the reduction and re-oxidation reactions of the oxygen carriers used in this study. Direct relationships are observed for the calculated values of both χ and λ with the experimentally derived O2 /CO evolution. The outcomes of this study can possibly influence the design of oxygen carriers with an improved performance in thermochemical processes for converting CO2 and utilizing solar energy.